Toxicity Test of Kirinyuh (Eupatorium odoratum L.) Leaf Extract Against Mortality of Golden Snail (Pomacea canaliculata) - Nurhasbah Nurhasbah; Safrida Safrida; Asiah MD (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
Golden snail (Pomacea canaliculata) is a freshwater snail that has potential as a pest. Golden snail are very dangerous because it can attack the immature rice, so it need to find the right way to control it. One of the right way to control golden snail is by giving plant molluscicide. Plant molluscicide is molluscicide that derived from plants that can be used to control pests and plant diseases, one of them is kirinyuh (Eupatorium odoratum L.). The aim of this research was to determine the effect of kirinyuh (Eupatorium odoratum L.) leaf extract against mortality of golden snail (Pomacea canaliculata). The hypothesis of this research was the giving of kirinyuh (Eupatorium odoratum L.) leaf extract effected againts mortality golden snail (Pomacea canaliculata). This research used experimental method by using pattern completely randomized design (CRD) with 6 treatments and 4 replicates that were concentration P0 (control), P1 10.000 ppm extract, P2 20.000 ppm, P3 30.000 ppm, P4 40.000 ppm and P5 50.000 ppm. The parameter measured was the number of mortality golden snail after 24 hours. Data was analyzed by analysis of variance (ANOVA) and test Significant Difference (LSD). The result showed that the giving of every different concentrations of kirinyuh leaf extract had significant (P 0.05) for mortality of golden snail (Pomacea canaliculata). This research also showed that the concentration kirinyuh leaf extract that could kill 100% of pest golden snail is the highest concentration that was 50.000 ppm. The conclusion of this research was the giving of kirinyuh leaf extract for 24 hours significantly affected againts mortality of golden snail, the higher concentration of extract increased mortality rate of golden snail. Key words: golden snail, leaf of kirinyuh, extract, mortality